Modern technique and technologies. MTT' 2010: Proceedings of the 16th International Scientific and Practical Conference of Students, Post-graduates and Young Scientists, April 12 - 16, 2010 Tomsk, Russia (Tomsk, TPU Press, 2010)
Заглавие с экрана